Penerapan Location Based Service Untuk Pemetaan Lokasi Pertanian Menggunakan Metode Rational Unified Process - Aditya Tri Nugraha; Rinda Cahyana (Jurnal Algoritma, 2023)
Garut Regency has 6,095 farmer groups, with so much data, suppliers find it difficult to find quality farmer groups and are located close together. Research at the Garut College of Technology has previously discussed geographic information systems for the general public, but no research has been found that applies the location-based service method. The purpose of this study is to provide information on the location of farmer groups spread across Garut Regency to facilitate access to information for suppliers by applying the location based service method. The method used for designing Android-based applications is the Rational Unified Process (RUP) methodology including the Inception, Elaboration, and Construction stages. The results of this study are in the form of a mobile-based application that provides information on the location of farmer groups spread across Garut Regency and has a critique or suggestion feature, so that users can provide suggestions to farmer groups in order to improve the quality of their business premises and commodity yields. Based on the results of functional suitability testing, it shows that the quality of the software is stated to be very high with a percentage value of 100%. This agricultural location mapping application can lead users to the exact location of the farm.